BIMG-07. PHARMACOLOGICAL ASCORBATE ENHANCES RADIATION AND TEMOZOLOMIDE EFFECTIVENESS IN GLIOBLASTOMA BY A MECHANISM MEDIATED BY REDOX ACTIVE IRON. (25th March 2021) - Allen, Bryan; Petronek, Michael; Monga, Varun; Bodeker, Kellie; Smith, Brian; Buettner, Garry; Greenlee, Jeremy; Smith, Mark; Spitz, Douglas; Cullen, Joseph; Magnotta, Vincent; Buatti, John
Abstract: Pharmacological ascorbate (P-AscH - ; high dose intravenous infusions of vitamin C generating milli-molar plasma concentrations) has re-emerged as an anti-cancer therapy. Phase 1 clinical trials combining P-AscH - with chemotherapy and ionizing radiation demonstrate safety and promising clinical outcomes in a variety of malignancies. In a first-in-human trial, subjects with newly diagnosed glioblastoma (GBM) and undetectable MGMT promoter methylation were treated with P-AscH -, ionizing radiation, and temozolomide. Results demonstrate median progression-free survival (PFS) of 10 months and median overall survival (OS) of 23 months, comparing favorably to historical GBM patients expressing MGMT. P-AscH - 's anti-cancer mechanism is dependent upon the presence of redox active labile iron. In the presence of redox active iron, the formation of hydrogen peroxide, which causes oxidative stress and eventual cell death, selectively forms in cancer cells. Treatment with P-AscH - increased cancer cells' labile iron pool, further enhancing sensitivity to P-AscH - . We investigated the capability of MR imaging (T2 * relaxation time) to measure the redox active iron and predict response to P-AscH - . T2 * relaxation time is influenced by in-field inhomogeneities, such as redox active paramagnetic iron. The active phase 2 trial evaluating P-AscH -, radiation, and temozolomide for GBM, obtains T2 * imaging prior to (baseline) and immediately after ascorbate infusion (NCT02344355). A preliminary analysis of the baseline scan for the first 15 subjects suggests those with faster GBM T2 * relaxation times (≤ 58 ms) have more redox active labile iron pools as well as an improved median PFS (11.4 months) compared to those with slower T2 * relaxation times (> 58 ms; median PFS of 8.5 months). Pre-clinical studies evaluating the effectiveness of iron nano-particle supplementation in GBM animal models are on-going. (Supported by P01 CA217797, R01 CA169046, U01 CA140206, T32 CA078586, P30 CA086862, as well as the Gateway for Cancer Research grant G-17–1500.)